Implementation of the Merdeka Campus Internship Program to Develop Self-Directed Learning - Sahri, Sahri; Akhyak, Akhyak; Agus Eko Sujianto (International Journal of Technology and Education Research, 2025)
The Merdeka Campus Internship Program at Yudharta Pasuruan University is part of an effort to enhance the quality of education by integrating academic theory and real-world practical experience in the workplace. Although the academic curriculum provides a foundation of knowledge, students often struggle to develop learning independence and professional skills when facing real challenges in the field. This issue encourages the need for a systematic and structured internship program to bridge the gap between theory and practice. The aim of this research is to analyze the design, implementation, and evaluation of the internship program in improving students' learning independence and their readiness to face the workforce. The research method used is descriptive-qualitative, with data collection through observations of internship activities, logbooks, weekly reports, and interviews with students, supervising lecturers, and industry supervisors. Data analysis is conducted by linking field findings to Kolb's Experiential Learning principles, which include concrete experience, reflection, conceptualization, and active experimentation. The research results show that the internship program effectively reinforces the principles of Experiential Learning, where students are able to apply theory to practice, reflect on experiences, develop improvement strategies, and enhance self-directed learning. The evaluations conducted collaboratively between lecturers and industry partners also strengthen the development of technical competencies and soft skills, including creativity, initiative, teamwork, and professionalism